Examining the Evolution of Management Accounting: A Qualitative Review - Harnani, Sri (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This qualitative review investigates the evolution of management accounting, focusing on its historical development, theoretical frameworks, and contemporary practices. The research aims to provide insights into the adaptive nature of management accounting in response to changing organizational needs, technological advancements, and societal trends. The methodology involves a comprehensive literature review encompassing historical analysis, theoretical perspectives, and empirical studies in the field of management accounting. Key findings reveal the historical roots of management accounting tracing back to the Industrial Revolution, with significant milestones including the emergence of cost accounting techniques, budgeting systems, and advanced methodologies like activity-based costing and strategic management accounting. The review also identifies theoretical frameworks such as agency theory, contingency theory, and institutional theory, offering diverse perspectives on the role and functioning of management accounting within organizations. Contemporary practices in management accounting emphasize strategic analysis, risk management, performance measurement, and the integration of financial and non-financial metrics. Technological advancements, particularly in information technology, have revolutionized decision support capabilities, enabling real-time monitoring and analysis of organizational performance. The synthesis of literature underscores the dynamic and multifaceted nature of management accounting, highlighting its pivotal role in facilitating strategic decision-making, enhancing organizational performance, and driving sustainable growth. The findings contribute to a deeper understanding of management accounting evolution and offer implications for practice and future research.